2021
DOI: 10.28991/cej-2021-03091748
|View full text |Cite
|
Sign up to set email alerts
|

Non-stationary Investigation of Extreme Rainfall

Abstract: Natural or human-induced variability emerged from investigation of the traditional stationary assumption regarding extreme precipitation analyses. The frequency of extreme rainfall occurrence is expected to increase in the future and neglecting these changes will result in the underestimation of extreme events. However, applications of extremes accept the stationarity that assumes no change over time. Thus, non-stationarity of extreme precipitation of 5, 10, 15, and 30 minutes and 1-, 3-, 6-, and 24-hour data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The four distributions of generalized extreme value, Gumbel, normal, and lognormal, have been used in this study to carry out the return level for a specific return period. Numerous researchers used these probability distributions for the analysis of return levels of hydro-meteorological variables [39][40][41][60][61][62][63][64]. The analysis of precipitation was carried out for the historical and projected period.…”
Section: Stationary and Nonstationary Frequency Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The four distributions of generalized extreme value, Gumbel, normal, and lognormal, have been used in this study to carry out the return level for a specific return period. Numerous researchers used these probability distributions for the analysis of return levels of hydro-meteorological variables [39][40][41][60][61][62][63][64]. The analysis of precipitation was carried out for the historical and projected period.…”
Section: Stationary and Nonstationary Frequency Analysismentioning
confidence: 99%
“…For instance, Aziz et al [39] focuses on the transient inconsistency in yearly as well as seasonal extreme rainfall in Turkey, which was investigated by using stationary and nonstationary frequency approaches. Sertac et al [40] studied the nonstationary investigation of extreme rainfall and observed that nonstationary (NST) models outperformed the stationary model at the 17 stations. Nashwan et al [41] investigated how a change in the environment (nonstationarity) affects the average and intensity of annual and seasonal rainfall in Malaysia and the magnitude of maximum rainfall at 2-, 10-, 25-, 50-, and 100-year return periods has increased at most of the stations.…”
Section: Introductionmentioning
confidence: 99%
“…Xavier et al (2019) used generalized extreme value (GEV) distribution with time‐varying parameters to study the trend for precipitation extremes over the last 30 years in the Paraná River basin, Brazil. Many studies have proved that time‐varying characteristics and return levels of extreme precipitation are better described by non‐stationary extreme value distributions compared with stationary distributions (Brown, 2018; Liu et al, 2022b; Oruc, 2021). However, there are still limited studies to apply non‐stationary extreme value distribution to investigate return levels of precipitation extremes at a large scale, especially for China.…”
Section: Introductionmentioning
confidence: 99%
“…Other investigations such as those of Rollenbeck et al (2021), Rollenbeck et al (2022) and, Vavrus et al (2022 also analyzed the maximum rainfall in Peru, specifically in the northern zone of Peruvian Pacific, but without reaching the contrast of any extreme value distribution with their respective parameters and the quantification of extreme events for different return periods. Due to the above, there is a need to know the parameters of the GEVD in rainfall of Peru and with greater scope in the northern zone, since as indicated by SENAMHI (2017b) the Pacific 5 and Pacific 6 hydrological regions of Peruvian northwest, they are the ones that are the most prone to extreme storm events, which are mainly influenced by the altitude and seasonality of rainfall (Oruc, 2021;Arriola et al, 2022;Fernandez-Palomino et al, 2022).…”
mentioning
confidence: 99%